A New Method for Evaluating the Diffusion of Ca2+ and OH- Ions through Coronal Dentin into the Pulp - Gandolfi, Maria Giovanna (Iranian Endodontic Journal, 2012)
Introduction: Ca(OH)2-containing/forming materials are conventionally used for indirect pulp-capping and are theoretically able to release Ca2+ and OH- ions for hydrolytic dissociation. However, no evidence exists for ion diffusion through the remaining coronal dentin. The aim of this study was to design an innovative experimental set-up to test the ability of Ca(OH)2-containing and Ca(OH)2-forming pulp-capping materials to generate pulpward Ca2+ and OH- ion fluxes through coronal dentin after indirect pulp-capping in vitro. Materials and Methods: Standardized class 1 cavities were prepared in erupted sound human molars. Pulp tissue was excised. A coronal Remaining Dentin Thickness (RTD) (1±0.2 mm thick) was prepared within an occlusal-to-pulp cavity system (coronal RD system). The whole system/sample was treated with 17% EDTA to remove the smear layer and the external surface was covered by nail varnish. Indirect pulp-capping was performed on coronal RDT using a conventional pulp-capping material covered by a glass ionomer cement, a composite and nail varnish. Chemically different Ca(OH)2 materials were used to test the reliability of the set-up. The leached Ca2+ and OH- ions were measured using ion-selective electrodes after soaking for 3 hours, 24 hours, and 7 days in deionized water (10 mL, 37°C). <span style="font-style: normal; font-family: "Times New Roman","serif"; color: black; font-size: 11pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: ZH-CN; mso-bidi-language: FA;" lang="X-NONE">Results: Calcium ions were detected and a rise in pH was observed in the treated water after a few hours for all tested materials. <span style="font-style: normal; font-family: "Times New Roman","serif"; color: black; font-size: 11pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: ZH-CN; mso-bidi-language: FA; mso-ansi-language: EN-US;">Conclusion<span style="font-style: normal; font-family: "Times New Roman","serif"; color: black; font-size: 11pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: ZH-CN; mso-bidi-language: FA; mso-ansi-language: EN-US;">: The experimental set-up proved to be an easy and effective method for testing the different Ca(OH)2-containing and Ca(OH)2-forming materials ability to induce a pulpward flux of calcium and hydroxyl ions through coronal remaining dentin after indirect pulp-capping. The new system will allow the screening of current pulp-capping materials.